The Development of Computer Multimedia Instruction on the Time Study in Mathematics Strand for Grade 4 Students - Watthanakul, Monthanan (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The objectives of this research were 1) to develop computer multimedia instruction on the time study in mathematics strand for grade 4 students to meet the 80/80 standard criteria, 2) to identify the efficiency index of the developed computer multimedia instruction, 3) to compare the academic achievement of the students who n taught with the computer multimedia instruction and those with the conventional lessons, and 4) to study the students’ satisfaction with the computer multimedia instruction. The sample for the study, drawn try using multi-stage sampling, consisted of 102 grade 4 students attending Anubansongkhla School during the second semester of the 2012 academic year. The instruments used in the study consisted of 1) the computer multimedia instruction on the time study in mathematics strand for grade 4 students, 2) a learning achievement test, 3) a questionnaire probing students’ satisfaction, 4) an evaluation form probing the efficiency of the computer multimedia instruction, and 5) learning plan for the topic of time. The data analysis used were percentage, arithmetic means, standard deviations and a T-test independent. The findings of the study revealed that 1) the developed computer multimedia instruction achieved the efficiency of 83.92/81.00, 2) the developed computer multimedia instruction showed the efficiency index of 0.58, 3) the students who were taught with the computer multimedia instruction showing higher learning achievement than those taught with the conventional lessons at 0.05 level of statistical significant, and 4) the students show a ‘very high level of satisfaction with the developed computer multimedia instruction ( = 4.76, S.D. = 0.43)